(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The Industrial Banks in most countries in the world plays an essential and vital role in developing the industrial sector due to its effective importance in the economic and social development. The research aims to study the ability of the Industrial Bank of Iraq to the growth and development of the mixed industrial sector companies through loans granted to them. In addition, the research seeks to study credit policies pursued by the Industrial Bank of Iraq to finance the mixed industrial sector companies. The data of the research has been collected from the financial statements of the Industrial Banks of Iraq for the period 2007-2011, and by means of questionnaire distributed to a sample of the mixed industrial sector companies in Iraq to investigate the real role of the bank in financing the companies of the mentioned sector. The major hypothesis of the research is that the role of the Industrial Bank of Iraq is limited in providing investment funding required to the mixed industrial sector companies in Iraq. The results generally indicate the limited role of the Industrial Bank of Iraq in granting the investment financing to the mixed industrial sector companies due to the weak governmental financing provided to the Industrial Bank. This negatively affects its activities to support these companies and consequently not granting any loans during period of the study, except the last year.